Age- and dose-dependent effects of an eicosapentaenoic acid-rich oil on cardiovascular risk factors in healthy male subjects - Cazzola, Roberta; Russo-Volpe, Samantha; Miles, Elizabeth A.; Rees, Dinka; Banerjee, Tapati; Roynette, Catherine E.; Wells, Solenne J.; Goua, Marie; Wahle, Klaus W.J.; Calder, Philip C.; Cestaro, Benvenuto (Atherosclerosis, 2007)
Supplementation with fish oils, rich in n − 3 polyunsaturated fatty acids, modifies cardiovascular risk factors. However, dose–response relationships are poorly defined and whether similar effects are seen in young and older subjects is not known. This study determined the effect of supplementing the diet of young and older male subjects with different amounts of an eicosapentaenoic acid (EPA)-rich oil. Healthy young (18–42 years) and older (53–70 years) males were randomized to placebo or 1.35, 2.7 or 4.05 g EPA/day for 12 weeks. There was no effect of EPA on blood pressure or on plasma total, LDL or HDL cholesterol. EPA lowered plasma triacylglycerols, with the maximal effect at the lowest dose. Plasma lipoperoxides decreased in all groups. EPA decreased the lag time of copper-induced lipoprotein peroxidation and the ratio of reduced to total glutathione in the older subjects. The highest dose of EPA increased soluble E-selectin in young subjects, while increasing EPA tended to decrease soluble intercellular adhesion molecule 1 in young and older subjects. Young and older males will gain cardiovascular benefit from increased intake of EPA. Young males are unlikely to suffer adverse consequences from high EPA intake, whereas older males may have an increased risk of lipoprotein peroxidation.